2021
DOI: 10.3390/fluids6110374
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Mass Fraction over the Turbulent Behaviour of an Incompressible Particle-Laden Flow

Abstract: The presence of spherical solid particles immersed in an incompressible turbulent flow was numerically investigated from the perspective of the particle mass fraction (PMF or ϕm), a measure of the particle-to-fluid mass ratio. Although a number of different changes have been reported to be obtained by the presence of solid particles in incompressible turbulent flows, the present study reports the findings of varying ϕm in the the turbulent behaviour of the flow, including aspects such as: turbulent statistics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
0
7
0
1
Order By: Relevance
“…The simulation setup was configured to maintain a Courant number less than 1, with a time step size equal to 1 × 10 −4 . This consideration ensures that the solution has a stable behavior during the simulation time ( [13,49,53]). Temporal integration was performed by using a backward scheme and the spatial discretisation was solved using second-order interpolation schemes for the gradient and divergence terms.…”
Section: Rdmentioning
confidence: 99%
“…The simulation setup was configured to maintain a Courant number less than 1, with a time step size equal to 1 × 10 −4 . This consideration ensures that the solution has a stable behavior during the simulation time ( [13,49,53]). Temporal integration was performed by using a backward scheme and the spatial discretisation was solved using second-order interpolation schemes for the gradient and divergence terms.…”
Section: Rdmentioning
confidence: 99%
“…The effect of particle loading on the turbulent structure, viz. streak spacing in turbulent channel flows, has been described by different authors 9,12,13 . Zhou et al 13 observed a non-monotonic behavior of streamwise fluid fluctuations with an increase in mass loading.…”
Section: Introductionmentioning
confidence: 98%
“…The authors observed very small attenuation even at mass loading of one for the copper particle of St = τ p U cl /δ = 70 where τ p is the particle relaxation time, δ is the halfchannel width, and U cl is the channel centerline velocity. Duque-Daza et al 9 performed the LES of turbulent channel flows for three different Reynolds numbers of Re τ = 180, 365, and 950. For mass loading of 2.96, a complete turbulence collapse was observed at Re τ = 180, while a negligible turbulence modification was observed at Re τ = 950.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis of variation of the apparent Kolmogorov constant with particle volume loading and the new methodology will provide insight to develop advanced models for two-phase turbulent flows. This work is important for the current scenario because many studies are performed at similar Reynolds numbers (∼ Re b = 5600) (Armenio, Piomelli & Fiorotto 1999;Kuerten & Vreman 2005;Kuerten 2006;Marchioli, Salvetti & Soldati 2008;Vreman et al 2009;Dritselis & Vlachos 2011;Zamansky, Vinkovic & Gorokhovski 2013;Duque-Daza, Ramirez-Pastran & Lain 2021; which are of practical importance.…”
Section: Introductionmentioning
confidence: 99%